Digital Rights as a New Dimension of Human Rights: Regulatory Challenges in the Era of Artificial Intelligence - Samosir, Hotlan (PT. Anagata Sembagi Education, 2025)
The rapid development of digital technology, especially through the integration of artificial intelligence (AI), has encouraged the birth of a new dimension of human rights, namely digital rights. These rights include the protection of digital identity, privacy, data security, and freedom of expression in cyberspace, which have not been fully accommodated by the national legal system. In practice, the non-transparent and discriminatory use of AI runs the risk of violating individual rights, especially in automated decision-making, mass digital surveillance, and the reproduction of content without attribution. Indonesia still faces normative and institutional vacancies, especially in the ITE Law, the Copyright Law (UUHC), and the Personal Data Protection Law (PDP Law), which have not integrated human rights principles substantively. This study uses a normative juridical method with a conceptual and legislative approach to examine the effectiveness of digital rights protection in the midst of AI development. It was found that the Indonesian legal system requires legal reform based on the principles of fairness, algorithmic accountability, and substantive justice. It is also necessary to establish an independent supervisory authority and harmonize national regulations with international standards. In conclusion, the recognition of digital rights as an integral part of human rights is an essential condition for the sustainability of a democratic state of law in an increasingly complex and autonomous digital era..